The Role of Personality Characteristics of the Leader in Business Organizations Entrepreneurship (Field Research) - سعيد سناء عبد الرحيم; علي فرح حسين (Journal of Economics and Administrative Sciences, 2018)
This research is aiming to find the effective role of the personality characteristics of the Leader in business organization entrepreneurship by studying the effect of the special dimensions of personality characteristics (neuroticism, extraversion, openness, Agreeableness, and conscientiousness) on business organizations entrepreneurship dimensions representing in the two main dimensions (entrepreneurship direction and strategic entrepreneurship) across field study was conducted in thirteen private colleges in Baghdad. The problem of the research relies in asking the question, is there an effect for Leader personality characteristics on business organizations entrepreneurship. and statistical methods have been used including (frequency distribution, arithmetic mean, standard deviation, coefficient of variation,…) as statistical program is used (SPSS v. 19), (Excel 2010) to reach results. The research has come into a set of theoretical and practical conclusions, most important of which is the organizations use the entrepreneurship to achieve customers satisfaction through improving the levels of presented services to them, and through the possessing of the leaders of these organizations of personality characteristics qualify them to reach the level of entrepreneurship in their work, where the respondents sample characterized with cooperation and love for others and acceptableness to them and also characterized diligence at work.